Nonsmoker assertive behavior against smoke exposure: Chinese and Korean American nonsmokers - Saw, Anne (Drug Alcohol Rev, 2017)
INTRODUCTION: Non-smokers’ assertive behaviour towards smokers by asking them not to smoke is important in promoting smokefree environments. Korean and Chinese Americans come from countries where most women are non-smokers and assertive behaviour may not be prevalent but may increase after migration due to social-ecological factors. This study assessed the extent to which Korean and Chinese American non-smokers ask someone not to smoke and associated factors. METHODS: The 2003 California Chinese American and Korean American Tobacco Use Surveys were analysed. Multivariate logistic regression analyses examined factors related to non-smoker self-reports that they asked someone not to smoke within the past year. RESULTS: Forty percent reported past year assertive behaviour against smoking, with higher rates among Koreans than Chinese (60.4% vs. 34.5%). Rates were also higher among those living with smokers (63.5%), ever exposed with a smokefree home rule (62.3%), recently exposed at work without a smokefree work policy (67.6%) and regularly exposed at other locations (52.3%). In combined multivariate analyses of both ethnic groups, assertive behaviour was associated with individual factors (single vs. married, tobacco exposure knowledge), family factors (living with smokers, exposed at home despite a smokefree rule), community factors (exposed at work with no smokefree policy, exposed at other locations) and cultural factors (Korean vs. Chinese ethnicity, lower acculturation). DISCUSSION AND CONCLUSIONS: Chinese and Korean American non-smokers report assertive behaviour against smoking, which is associated with social-ecological factors. Results help identify target groups and strategies for future intervention, including the need to implement or enforce smokefree environments and promote empowerment.